Gestational Trophoblastic Diseases at a Tertiary care Hospital in Nepal: A Five Years Retrospective Study - Gautam, Nikita; Makaju, Ramesh; Basnet, Dipika; Lama, Binita; Maharjan, Prem Bahadur; Shakya, Sunila (Nepalese Medical Journal, 2022)
Introduction: Gestational trophoblastic diseases, because of their diverse presentation and the malignant lesions being associated with recurrence, metastasis, and mortality, early diagnosis is important with the help of ultrasonogram preoperatively, serial Beta human chorionic gonadotropin, and histopathological examination for prompt treatment and timely management of the patients. The study aimed to identify the overall prevalence and relative frequencies of Gestational trophoblastic diseases and to assess the association of different gestational trophoblastic diseases with maternal age, parity, and gestational age. Materials and Methods: This is a retrospective cross-sectional study conducted for five years from January 2016 to December 2020 in the Department of Pathology, and Department of gynecology and obstetrics of Dhulikhel Hospital, Kavre Nepal. This study included a spectrum of gestational trophoblastic diseases. All the details were obtained from the patient’s record file and register book. Results: Out of 65 cases, the most common was Hydatidiform mole with 59 (90.78%) cases. Bleeding per vagina was the most common clinical presentation. The most commonly affected age group was 21-25 years. Most of the gestational trophoblastic diseases were detected in the first trimester and primigravida. Conclusions: Any pregnant woman presenting with abnormal uterine bleeding should be evaluated for the presence of underlying Gestational trophoblastic disease. Beta-hCG is a sensitive marker, however, histopathology remains a gold standard modality for the detection of gestational trophoblastic diseases. The judicious use of ultrasonograms and appropriate clinicopathological approach helps the clinician to decide the treatment modalities, especially between evacuation and hysterectomy.